Elementary charge measurement by water electrolysis - João Bernardes da Rocha Filho (Caderno Brasileiro de Ensino de Física, 2009)
This article presents an educational technique recommended for High School students or undergraduates on Physics or Chemistry education, which allows the measurement of the elementary charge through  water  electrolysis.  The  proposed  experiment  wraps material of easy attainment, the results have sufficient precision for the    education    purposes,    and    its    realization    promotes   interdisciplinarity, since it wraps knowledge of different areas. In addition,  this  article  presents  results  obtained  by  pupils  in laboratory classrooms.